2022
DOI: 10.1111/1752-1688.13040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Models Performance on Simulating Reservoir Outflow: A Case Study of Two Reservoirs in Illinois, U.S.A.

Abstract: Reservoir outflow is an important variable for understanding hydrological processes and water resource management. Natural streamflow variation, in addition to the streamflow regulation provided by dams and reservoirs, can make streamflow difficult to understand and predict. This makes them a challenge to accurately simulate hydrologic processes at a daily scale. In this study, three Machine Learning (ML) algorithms, Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
(155 reference statements)
2
8
0
Order By: Relevance
“…The predictors utilized in this study to construct the RF model, their usage proxy and their ranks across the reservoirs based on permutation accuracy importance (Strobl et al, 2007), are shown in Table 2. These type of predictors have been widely used in the literature for example, Qie et al (2022); Tounsi et al (2022). Optimized RF models were obtained for each reservoir of the experiment.…”
Section: Estimating Non-consumptive Demand With a Surrogate Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictors utilized in this study to construct the RF model, their usage proxy and their ranks across the reservoirs based on permutation accuracy importance (Strobl et al, 2007), are shown in Table 2. These type of predictors have been widely used in the literature for example, Qie et al (2022); Tounsi et al (2022). Optimized RF models were obtained for each reservoir of the experiment.…”
Section: Estimating Non-consumptive Demand With a Surrogate Modelmentioning
confidence: 99%
“…Reservoir operation signal can be defined as the difference between the regulated and natural streamflow time series, where the latter would have been measured without the reservoir (Brunner & Naveau, 2023). There are numerous works that reconstruct the reservoir operation signal from observed streamflow time series measured downstream of a reservoir, such as the use of wavelet transform (Shiau & Huang, 2014; White et al., 2005), artificial neural networks (Ehsani et al., 2016; Qie et al., 2022), fuzzy rules (Coerver et al., 2018), harmonic regression models (Turner et al., 2021), Random forest (RF) and Support Vector Machines (Qie et al., 2022), generalized additive models (Brunner & Naveau, 2023), among others. With this in mind, it remains to be seen how useful the S2023 would be in conjunction with ML techniques in HMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Shamim et al (2016) showed that localized linear ML models are capable of predicting reservoir levels in Pakistan. Qie et al (2022) analyzed reservoir outflow for two sites in Illinois, USA and showed promising results using multiple different statistical techniques. ML models are also frequently used in water quality research, including recent studies in Vietnam (Nguyen et al, 2021), Hong Kong (Deng et al, 2021), and Ghana (Ewusi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the end, all the trees are combined into the so-called forest as it averages all predictions to produce a final output value. Considering its strengths, RF has been increasingly applied in reservoir modelling studies (e.g., Yang et al, 2016;Li et al, 2020;Qie et al, 2022).…”
Section: Random Forest (Rf)mentioning
confidence: 99%